What versus where: Investigating how autobiographical memory retrieval differs when accessed with thematic versus spatial information. Issue 9 (2nd September 2017) - Sheldon, Signy; Chu, Sonja
ABSTRACT: Autobiographical memory research has investigated how cueing distinct aspects of a past event can trigger different recollective experiences. This research has stimulated theories about how autobiographical knowledge is accessed and organized. Here, we test the idea that thematic information organizes multiple autobiographical events whereas spatial information organizes individual past episodes by investigating how retrieval guided by these two forms of information differs. We used a novel autobiographical fluency task in which participants accessed multiple memory exemplars to event theme and spatial (location) cues followed by a narrative description task in which they described the memories generated to these cues. Participants recalled significantly more memory exemplars to event theme than to spatial cues; however, spatial cues prompted faster access to past memories. Results from the narrative description task revealed that memories retrieved via event theme cues compared to spatial cues had a higher number of overall details, but those recalled to the spatial cues were recollected with a greater concentration on episodic details than those retrieved via event theme cues. These results provide evidence that thematic information organizes and integrates multiple memories whereas spatial information prompts the retrieval of specific episodic content from a past event.